Association of Angiotensinogen (M235T) Gene Polymorphism with Blood Pressure Lowering Response to Angiotensin Converting Enzyme Inhibitor (Enalapril) - Kamna Srivastava; Sudhir Chandra; Jagriti Bhatia; Rajiv Narang; Daman Saluja (Frontiers Media S.A., 2012)
Purpose: It has been suggested that genetic backgrounds, which have an association with essential hypertension, may also determine the responsiveness to ACE inhibitor. We determined the association of angiotensinogen (M235T) gene polymorphism with essential hypertension and the relationship between polymorphism in the angiotensinogen (M235T) gene and blood pressure response to ACE inhibitor (Enalapril) in patients with essential hypertension from northern Indian subjects. Methods: 250 patients with essential hypertension and 250 normal healthy controls from Delhi and surrounding areas were recruited for the investigation. Blood pressure was recorded before and after 6 weeks of treatment with ACE inhibitors, Enalapril. Genotyping were carried out by polymerase chain reaction and Restriction fragment length polymorphism technique. Results: Statistically significant association of T allele was observed with essential hypertension [x2 = 14.67, p = 0.00013, Odds ratio = 1.76 (1.3-2.32) at 95% CI], the relative risk at 95% CI being 1.28 (1.2-1.54). The decrease in systolic blood pressure and diastolic blood pressure after six weeks of treatment of the patients carrying TT genotype (SBP = 26±17.4 mmHg, DBP = 14.83±7.6mmHg) were greater than the groups carrying MT (SBP = 3.0±7.8 mmHg, DBP =6.2±3.0 mmHg) and MM genotypes (SBP = 1.2±0.8 mmHg, DBP = 0.10±12.1 mm Hg. Conclusions: The angiotensinogen (M235T) gene polymorphism is significantly associated with essential hypertension. Patients carrying TT genotype had higher blood pressure lowering response when treated with ACE inhibitor, Enalapril than those carrying MM and MT genotypes suggesting that the T allele may be a possible genetic marker for essential hypertension. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.